The effect of software engineers’ personality traits on team climate and performance: A systematic literature review - Soomro, Arjumand Bano; Salleh, Norsaremah; Mendes, Emilia; Grundy, John; Burch, Giles St. J.; Nordin, Azlin (Elsevier, 2016)
Context: Over the past 50years numerous studies have investigated the possible effect that software engineers’ personalities may have upon their individual tasks and teamwork. These have led to an im- proved understanding of that relationship; however, the analysis of personality traits and their impact on the software development process is still an area under investigation and debate. Further, other than per- sonality traits, “team climate” is also another factor that has also been investigated given its relationship with software teams’ performance. Objective: The aim of this paper is to investigate how software professionals’ personality is associated with team climate and team performance. Method: In this paper we detail a Systematic Literature Review (SLR) of the effect of software engineers’ personality traits and team climate on software team performance. Results: Our main findings include 35 primary studies that have addressed the relationship between per- sonality and team performance without considering team climate. The findings showed that team climate comprises a wide range of factors that fall within the fields of management and behavioral sciences. Most of the studies used undergraduate students as subjects and as surrogates of software professionals. Conclusions: The findings from this SLR would be beneficial for understanding the personality assessment of software development team members by revealing the traits of personality taxonomy, along with the measurement of the software development team working environment. These measurements would be useful in examining the success and failure possibilities of software projects in development processes. General terms: Human factors, performance.